Metal chelating activity of Centella asiatica - Mohd Salim, Roshan Jahn; Amid, Azura; Adenan, Mohd Ilham; Sued, Anee Suryani (2010)
Centella asiatica (CA), a potent antioxidant, was studied for its potential as a neuroprotective agent to fight against oxidative damage by reactive oxygen species (ROS) to neuronal cells which eventually lead to neurodegenerative diseases such as Alzheimer's and Parkinson disease. The build-up of an iron gradient in conjunction with ROS is thought to constitute a major trigger in neuronal toxicity and demise in these diseases. The limited number of neuroprotective study carried out so far indicate the iron chelation therapy could be a viable neuroprotective approach for neurodegenerative disorders. The metal chelating potency can be determined by assessing the ability of neuroprotective agents to compete with ferrozine for Fe(II) ions. Ferrozine forms complexes with Fe(II) producing a red color that can be measured quantitatively at 562 nm and addition of iron chelators interferes with the formation of ferrous and ferrozine complexes in a concentration-dependent manner. The IC50 value, concentration re quired for 50% inhibition of the iron-ferrozine complex, was measured. Methanolic and aqueous extract of CA was prepared by conventional soxhlet extraction (40-60*C, ratio: 1:30(w/v), 15 hours). The IC50 of methanolic and aqueous extract obtained was 0.26mg/ml and 0.69mg/ml respectively. The (-)-epigallocatechin-3-gallate (AGCG), Major component of green tea reported to have induce neuroprotection and neurorescue both in vitro and in vivo was used as positive control. Further, Response Surface Methodology was used to determine the optimum CA extraction condition that give optimum metal chelating activity. Experiments were designed according to Central Composite Design with four factors (time, temperature, ratio of raw material to solvent and agitation speed) and six central points that derived total 30 runs. Run 17 (25*C, ratio: 1:45(w/v), 1.5 hours at 200 rpm) gave the optimum chelating activity with IC50 0.093 mg/ml.